2005
DOI: 10.1111/j.1742-6723.2005.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in trauma team activation criteria between hospitals within the same region

Abstract: The criteria for TTA differ between hospitals within the same region. The criteria currently used will result in over-triage of trauma patients, but this might be of benefit in training the trauma team in centres that do not see a large volume of trauma patients. There are several advantages in standardization of criteria including optimization of patient care, training, research and audit. Further work is needed to validate existing criteria for use throughout the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
18
0
2
Order By: Relevance
“…Studies from Great Britain, Denmark, and Australia have shown wide variation with respect to TTA criteria within the same country and region, despite comparable trauma populations [32-34]. As evident in our study, it is not clear why hospitals choose different "cut-offs", but tradition rather than evidence was cited as a possible explanation [30,31].…”
Section: Discussionmentioning
confidence: 60%
“…Studies from Great Britain, Denmark, and Australia have shown wide variation with respect to TTA criteria within the same country and region, despite comparable trauma populations [32-34]. As evident in our study, it is not clear why hospitals choose different "cut-offs", but tradition rather than evidence was cited as a possible explanation [30,31].…”
Section: Discussionmentioning
confidence: 60%
“…Even if the paediatric patient is ambulatory at scene with normal physiology and minor or no apparent injury, if the treating paramedic is in doubt, they are to transport the child to a trauma centre. Although this results in over‐triage, given the comparatively small incidence of paediatric trauma in Australia, it could be asserted that over‐triage can have the positive effect of facilitating trauma team training . Major trauma presentations comprise an extremely small percentage of overall emergency department (ED) presentations in the majority of hospitals, with injury overall accounting for 6% of the 6.7 million Australian ED presentations in 2006–2007…”
Section: Discussionmentioning
confidence: 99%
“…Surveys demonstrate that significant variation exists among the composition and activation criteria for trauma teams outside of the United States 3,4. Such variation is not known to occur within the U.S. but is highly likely.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for internal trauma team activation and degree of response vary by hospital 3,4. Limited data exist for determining appropriate internal trauma team response 512.…”
Section: Introductionmentioning
confidence: 99%